An Engineered Protein Adhesive with Properties of Tissue Integration and Controlled Release for Efficient Cartilage Repair. Issue 12 (5th May 2021) - Zhang, Jinrui; Li, Bo; Zuo, Jianlin; Gu, Rui; Liu, Bin; Ma, Chao; Li, Jingjing; Liu, Kai
Abstract: Cartilage damage is a prevalent health concern among humans. The inertness of cartilage, the absence of self‐healing properties, and the lack of appropriate repair materials that integrate into the tissue pose a significant challenge for cartilage repair. Thus, it is important to develop novel soft biomaterials with strong tissue adhesion and chondrogenic capabilities for cartilage repair. Herein, a new type of protein adhesive is reported that exhibits superior cartilage repair performance. The material is fabricated by the electrostatic combination of chondroitin sulfate (CS) and positively charged elastin‐like protein, which is derived from natural components of the extracellular matrix (ECM). The adhesive showed robust adhesion properties on different tissue substrates, offering a favorable environment for cartilage tissue integration. Noncovalent bonding between CS molecules in the glue allows for its controlled release, which is required for efficient chondrogenic differentiation. When implanted into a rat model of cartilage defect, this protein adhesive exhibited beneficial healing effects, as evidenced by enhanced chondrogenesis, sufficient ECM production, and lateral integration. Therefore, this engineered protein complex is a promising candidate for translational application in the field of cartilage repair. Abstract : A novel multifunctional protein adhesive is fabricated by the electrostatic combination of chondroitin sulfate and positively charged elastin‐like protein. It shows robust adhesion property and controlled release effect. When implanted into a cartilage defect model, it effectively promotes chondrogenesis and lateral tissue integration in vivo, providing a promising candidate for translational application in the field of cartilage repair.